Teaching listening comprehension in the EFL classroom - Csukás Erzsébet (1997)
In the first chapter I am writing about the listening skill itself. I am explaining the importance of teaching listening in the EFL classroom. I also enumerate the difficulties of learning to listen. The second chapter is about the materials that a teacher can use for listening activities. It is a hard work for fhe teacher to select the best material, so I examined the advantages and disadvantages of the possible choices. Both the third and the fourth chapter are dealing with the listening tasks including the plans for the exercices. The fifth chapter shows the stages how a listening lesson takes place in the EFL classroom. In the subchapter titled "Independent listening" I am mentioning the listening activites for entertainment. The main idea of the last chapter is the problems of learning to listen. This chapter gives some advice how we, teachers can solve the difficulties. I would like to justify with my research that the most important stage in listening comprehension is the pre-listening stage.